PENGEMBANGAN SOAL PELEVELAN LITERASI MATEMATIKA KONTEKS PERSONAL UNTUK SISWA KELAS VIII SMP - Mahfudhoh, Rif’atul; Susanto, Susanto; Trapsilasiwi, Dinawati (Department of Mathematics Education , University of Jember, 2017)
Abstract. The purposes of this research are developing mathematical literacy test items of personal context for eight grade students which are valid and reliable. This type of research is a development study consisting of 4 stages, namely: (1) preliminary stage that determines the area and the subject of trial. The area of ​​the test subject in SMP Nuris Jember is the students of class VIII C and 6 students of class VIII B. (2) stage self evaluation is designing the problem. Problems are developed as many as 5 questions, 2 questions at the first level, 2 questions at the second level,, and 1 question at the third level. Design of the questions at this stage is prototype 1. (3) prototyping stage, prototype 1 will be validated by validator. Problems that have been validly named prototype 2. Prototype 2 will be tested to 6 students of class VIII B in small group stage. In the small group stage there was only one student who commented on the questionnaire and 5 students had understood the math literacy questions. Problems are revised based on readability test recommendations. The result of the revision based on the test is called prototype 3. (4) field test stage is the test phase on the students of class VIII C. The results of the stage are analyzed to meet the criteria reliable. Problem that has been reliably named prototype 4. Based on the results of the validation data analysis in the average (Va) is 2.2 with the category is quite valid so it needs to be revised. After the problem is revised, the validator validates again with the average result (Va) is 3 with very valid category. Reliability test results by dividing the test subject into 2 parts randomly with reliabilty value is 0.64 and 0.63 with high category. From the results of the analysis, the problems that have been developed have valid and reliable criteria. Keywords: Test items development, mathematical literacy, PISA, personal context